Periodontal microbiota and phospholipases: The Oral Infections and Vascular Disease Epidemiology Study (INVEST). Issue 2 (October 2015) - Boillot, Adrien; Demmer, Ryan T.; Mallat, Ziad; Sacco, Ralph L.; Jacobs, David R.; Benessiano, Joelle; Tedgui, Alain; Rundek, Tatjana; Papapanou, Panos N.; Desvarieux, Moïse
Abstract: Objective: Periodontal infections have been linked to cardiovascular disease, including atherosclerosis, and systemic inflammation has been proposed as a possible mediator. Secretory phospholipase A2 (s-PLA2) and Lipoprotein-associated PLA2 (Lp-PLA2) are inflammatory enzymes associated with atherosclerosis. No data are available on the association between oral microbiota and PLA2s. We studied whether a relationship exists between periodontal microbiota and the activities of these enzymes. Methods: The Oral Infection and Vascular Disease Epidemiology Study (INVEST) collected subgingival biofilms and serum samples from 593 dentate men and women (age 68.7 ± 8.6 years). 4561 biofilm samples were collected in the two most posterior teeth of each quadrant (average 7/participant) for quantitative assessment of 11 bacterial species using DNA–DNA checkerboard hybridization. Mean concentration of s-PLA2 and activities of s-PLA2 and Lp-PLA2 were regressed on tertiles of etiologic dominance (ED). ED is defined as the level of presumed periodontopathic species/combined level of all eleven species measured, and represents the relative abundance of periodontopathic organisms. Analyses were adjusted for age, sex, race/ethnicity, education, smoking, BMI, diabetes, LDL cholesterol and HDL cholesterol, and systolic blood pressure. Results: Higher levels of s-PLA2 activity were observed across increasing tertiles of etiologic dominance (0.66 ± 0.04 nmol ml −1  min −1, 0.73 ± 0.04 nmol ml −1  min −1, 0.89 ± 0.04 nmol ml−1 min−1; p < 0.001), with also a trend of association between Lp-PLA2 activity and ED (p = 0.07), while s-PLA2 concentration was unrelated to ED. Conclusion: Increasingly greater s-PLA2 activity at higher tertiles of etiologic dominance may provide a mechanistic explanatory link of the relationship between periodontal microbiota and vascular diseases. Additional studies investigating the role of s-PLA2 are needed. Highlights: Etiologic dominance is the relative predominance of causative/over other bacteria. Etiologic dominance was independently associated with higher levels of s-PLA2 activity. Lp-PLA2 activity was unrelated to etiologic dominance. It may mark greater inflammatory activity, which could contribute to atherosclerosis.